Inequitable care delivery toward COVID-19 positive people of color and people with disabilities. - Danbi Lee; Paula M Kett; Selina A Mohammed; Bianca K Frogner; Janice Sabin (Public Library of Science (PLoS), 2023)
This study aimed to explore provider observations of inequitable care delivery towards COVID-19 positive patients who are Black, Indigenous, and Other People of Color (BIPOC) and/or have disabilities and to identify ways the health workforce may be contributing to and compounding inequitable care. We conducted semi-structured interviews between April and November 2021 with frontline healthcare providers from Washington, Florida, Illinois, and New York. Using thematic analysis, major themes related to discriminatory treatment included decreased care, delayed care, and fewer options for care. Healthcare providers' bias and stigma, organizational bias, lack of resources, fear of transmission, and burnout were mentioned as drivers for discriminatory treatment. COVID-19 related health system policies such as visitor restrictions and telehealth follow-ups inadvertently resulted in discriminatory practices towards BIPOC patients and patients with disabilities. As patients experience lower quality healthcare during the pandemic, COVID-19-related restrictions and policies compounded existing inequitable care for these populations.